Phenomena of Corruption as A Social Pathology: A Review on Legal Sociology - Muhammad Rahjay Pelengkahu; Fajri M Kasim (Jurnal Hukum Prasada, 2023)
This research examines the factual issues of eradicating and legal enforcement of corruption in Indonesia. In addition, the phenomenon of corruption as a social sickness is evaluated from the perspective of legal sociology research. Utilizing a descriptive-analytical research approach, literature studies are conducted to collect a variety of trustworthy resources and information. The study's findings indicate that the problem of eradicating and enforcing anti-corruption laws in Indonesia has become a cycle of corruption that will not end unless the state undertakes supremacy-reform initiatives in three areas: socio-cultural, legal instruments, and institutional-structural-functional. Corruption has become societal cancer that affects the development of legal culture in society. Corruption is viewed as a structural functionalism framework. Deviant conduct of officials v from a breach of the social structure's functioning.